Perusakan di Lingkungan Publik (Vandalisme) - M. Rafi Aufa HSB; Khalid Khalid (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the legal arrangements related to vandalism in the criminal law code (KUHP) in Indonesia, the social, economic and environmental impacts of vandalism in the public environment, law enforcement against acts of vandalism in the public environment, as well as a comparison of legal arrangements and handling cases of vandalism in Indonesia with other countries. The results of this study reveal that legal arrangements related to vandalism in Indonesia involve the creation, implementation and enforcement of legal rules that regulate the relationship between individuals, groups and institutions in society. The Indonesian Criminal Code (KUHP) provides relevant articles to deal with acts of vandalism, with a variety of sanctions depending on the circumstances of the case. Acts of vandalism in the public sphere have broad and complex impacts in social, economic and environmental aspects. Socially, vandalism disrupts social harmony and undermines community values. From an economic perspective, vandalism causes significant financial losses for owners of damaged facilities. In the environmental aspect, vandalism affects public awareness of environmental protection. The effectiveness of law enforcement against vandalism still requires improvement in terms of investigations, fair court decisions, and community cooperation with law enforcement officials. Doodling is classified as vandalism because it is against the law and has widespread negative impacts, including social, economic and environmental impacts. Keywords vandalism, legal arrangements, legal effectiveness